PENGARUH NPF, FDR, CAR, BOPO TERHADAP ROE BANK SYARIAH - Handayani, Dini; Rosyidah, Norma; Rani, Rani (Universitas KH. A. Wahab Hasbullah, 2024)
The research objective is to serve as a source of information regarding the influence of NPF, FDR, CAR, BOPO, on ROE of Islamic commercial banks. knowing the effect of Non Performing Financing (NPF), Financing to Deposit Ratio (FDR) and Capital Adquacy Ratio (CAR) to Return On Equity (BOPO) Operational Expenses and Operational Income (ROE) of Islamic banks either partially or partially simultaneously. This research is a quantitative research with an explanatory approach. The population in this study are all Islamic Commercial Banks in Indonesia. Deep sample This research was conducted by purposive sampling which resulted in a sample of 15 banks General Sharia. The data source in this study is secondary data taken from reports (OJK). Data collection was taken in the Times Series for six years. Data analysis was performed by carrying out multiple linear regression tests with SPSS which includes descriptive statistical tests, Classical Assumption Test, T Test and F Test. This study resulted that the effect of NPF on ROE obtained a T value of -0.538 with a significance of 0.686 so that Tcount > Ttable (2.446) and a significance of 0.686 > 0.05. So that the NPF has a negative effect and is not significant. Influence FDR on ROE obtained a t value of -5.754 with a significance of 0.110 so that T count > Ttable (- 5.754> 2.446) and a significance of 0.110 > 0.05 so that FDR has a negative effect and does not significant to ROE. The effect of CAR on ROE obtained a T value of -7,994 with a significance of 0.079 so that T count < T table (-7,994 > 2,446) and a significance of 0.079 > 0.05 so that CAR has a negative effect and is not significant on ROE. The effect of BOPO on ROE obtained a value of -29,744 with a significant 0.021 so that T count > T table (2,446) is significant 0.021 Ttable (691,841 > 2,446) and a significance of 0.029 > 0.05 so that simultaneously NPF, FDR, CAR and BOPO had a positive and significant effect on ROE Keywords: : NPF, FDR ,CAR, BOPO, Islamic Bank